Implementation of A Learning Management System using Prompt Engineering Horizon Artificial Intelligence in State Senior High School 1 Siau Barat - Alfrits Patrick Gunde; Harrychoon Angmalisang; Hiskia Kamang Manggopa; Parabelem Tinno Dolf Rompas (International Journal of Information Technology and Education, 2026)
Prompt in artificial intelligence is one of the terms in technology that is currently often discussed by academics, becoming a weapon in producing a digital work and has an important role in artificial intelligence. Prompt is a command spoken by humans to machines to produce digital work. In a broad view, prompt is the art of designing science and a compass to guide humans in using artificial intelligence. This study aims to maximize Prompt Engineering Horizon Artificial Intelligence to create a learning management system in SMA Negeri 1 Siau Barat. This study uses the method This study uses the Research and Development (R&D) method with the ADDIE development model. The application of the learning management system to Teachers and Students of SMA Negeri 1 Siau Barat is the result of this research, where the prompt is made into a programming language coding arrangement and becomes a neat and ready-to-use web-based learning management system application. The implementation of this application is new and the first for teachers and students of SMA Negeri 1 Siau Barat and has a positive impact on the understanding and use of technology. On the other hand, this system also allows teachers and students to use smartphones optimally in the school environment for learning.